1994
DOI: 10.1164/ajrccm.150.2.8049842
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in lung injury after combined surfactant and high-frequency ventilation.

Abstract: Previous studies demonstrated that high-frequency oscillatory ventilation (HFOV) begun at birth limits the development of alveolar proteinaceous edema in premature monkeys at risk for hyaline membrane disease (HMD). We hypothesized that exogenous surfactant combined with HFOV would lead to even further reductions in edema. Twenty Macaca nemestrina monkeys were delivered at 134 d gestation (term = 168 d) and treated with either HFOV or conventional mechanical ventilation (CMV) from the first breath; modified bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 0 publications
2
46
2
Order By: Relevance
“…Similarly, Hilgendorff et al [21] in an animal model showed that open-lung ventilation alone did better than surfactant and conventional ventilation. Human data confirmed the efficacy of HFOV recruitment maneuver in improving both functional lung capacity [22,23] and inflammatory lung profiles [24,25]. Furthermore, in two recent randomized controlled trials comparing HFO with CMV [7,8], ELR during HFOV allowed the number of repeated surfactant doses in VLBW infants with RDS to be reduced compared to infants assigned to conventional ventilation who were not submitted to a lung recruitment attempt.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, Hilgendorff et al [21] in an animal model showed that open-lung ventilation alone did better than surfactant and conventional ventilation. Human data confirmed the efficacy of HFOV recruitment maneuver in improving both functional lung capacity [22,23] and inflammatory lung profiles [24,25]. Furthermore, in two recent randomized controlled trials comparing HFO with CMV [7,8], ELR during HFOV allowed the number of repeated surfactant doses in VLBW infants with RDS to be reduced compared to infants assigned to conventional ventilation who were not submitted to a lung recruitment attempt.…”
Section: Discussionmentioning
confidence: 77%
“…It should be stressed that all these apparently disappointing reports refer to acute respiratory distress syndrome, or meconium injury. Preventive strategies of high frequency oscillatory ventilation [42], HFOV combined with exogenous surfactant [43] in premature baboons, and tidal liquid ventilation in preterm lambs [44] clearly reduce histologic lung injury. Recently, Kinsella et al [45] compared HFOV, PLV, and CMV after surfactant therapy in extremely premature lambs.…”
Section: Discussionmentioning
confidence: 99%
“…The delay between birth and surfactant-HFOV use, which may blunt the benefits of HFOV [5] is often a major difference between the procedures used in animal experiments and clinical trials. Starting HFOV at birth appears to be preferable in order to obtain any possible benefits of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…A pulmonary benefit of using HFOV with a high-volume strategy (HVS), compared with CV, has been shown without the use of exogenous surfactant in early studies [3] and more recently, in combination with exogenous surfactant [4,5]. The benefits of HFOV include a decrease of inflammatory mediators, which are early predictors of the development of CLD [6,7].…”
Section: Animal Experimentsmentioning
confidence: 99%